The role of toxicology in climate change: Understanding the risks of novel environmental toxins - Esther Ugo Alum (Sustainable Environment)
Climate crisis intensification contributes to reshaping toxicological landscapes, elevating human and ecological health hazards through environmental toxin emergence and change. Increasing temperatures, altered precipitation patterns, and melting permafrost remobilize and amplify toxins and have particularly severe effects on vulnerable populations, including coastal and indigenous communities. Assessment of the complex, climate-driven toxicological hazards requires an adaptive approach to toxicology that couples interdisciplinary and systems-level strategies. This commentary focuses on how climate change alters the toxicological landscape by redistributing and transforming contaminants such as heavy metals, persistent organic pollutants, and biotoxins as well as introducing novel environmental toxins, and heightening health risks for vulnerable populations. This study used data published in 2017–2024 from reliable scientific databases like Scopus, Web of Science, and ScienceDirect. The study emphasizes the need for adaptive toxicology frameworks to assess and mitigate climate-induced hazards, advocating for interdisciplinary collaboration and policy reform to promote proactive solutions.